Jay & Silent Bob reboot [videorecording (DVD)] - Smith, Kevin, 1970-; Smith, Kevin, 1970-; Smith, Kevin, 1970-; Mewes, Jason, 1974-; Smith, Harley Quinn; Benoist, Melissa (Lionsgate, 2020)
When stoners Jay and Silent Bob find out that Hollywood is going to do a reboot of an old movie based on them, they set out on a mission to stop the movie from being made.